Linkages between government spending, growth, and poverty in Uganda and Tanzania - Fan, Shenggen (Cornell University, 2007)
This case study presents a synthesis of the links between government spending— in areas such as agricultural research and development (R&D), irrigation, rural education, and infrastructure (including roads, electricity, and telecommunications)— and economic growth and poverty reduction in Uganda and Tanzania. The findings of this case study are intended to help explain how government spending on key investments can help meet the broader policy goals of improved growth and poverty reduction through various channels. This study, using a common framework, seeks to broaden and deepen understanding of the mechanisms through which government investment results in pro-poor economic growth. The overall picture for public investment can be summarized as follows: For Tanzania, the results of household survey data show that investments in agricultural research, roads, and education have large effects on income growth. No clear pattern distinguishes the measured impacts for highand low-potential areas. In many high-potential areas, returns to investments are still high with no signs of diminishing marginal returns, which suggests that public investment has been insufficient in all regions. Nonetheless, the results demonstrate that there are opportunities to improve the growth and poverty impacts of total public spending through better regional targeting of specific types of investment. For Uganda, district-level data show that government spending on agricultural research and extension had the largest impact on agricultural productivity, followed by spending on rural roads. Across regions, the study demonstrated that investments in the northern region (a poor region) have the potential to contribute the most to reducing poverty, whereas in the western region (a high-potential region), most types of investment have the potential to achieve the highest returns in improving agricultural productivity. Your assignment is to recommend a public sector investment strategy for rural infrastructure to be considered by the government of one of the two countries discussed in this case.